Departamento de economia solidária do BNDES: uma proposta de melhorias na estrutura organizacional e no modelo de apoio a empreendimentos de baixa renda - Barbosa, Rodrigo Correia (2013)
BNDES, throughout its history, has sought to expand the scope of its actions, using new forms of multiplication of their financial support and this relentless pursuit of innovative initiatives keeps Institution in constant transformation and consolidates its position to service needs and expectations of the Brazilian nation. The Solidarity Economy Department of the BNDES (DESOL) acts in supporting social economy enterprises, seeking employment and income generation and economic inclusion of low-income population. Historically, the performance of this Department was happening directly between BNDES and the beneficiary, following the same steps applied to the bigger companies and with intensive use of staff resources and time. Recently, in order to expand the scope of its activities, the DESOL implemented a new way of acting, with emphasis on building partnerships to ensure the expansion of the range to your target audience in a sustained way, and under a systemic which resulted in changing the process of lending to these projects, which resulted in a breakthrough in terms of scope and disbursement. However, some bottlenecks can already be perceived and this paper presents proposals for improvements in the structure and form of action that considers various constraints of the Department and provides possibilities for implementation in the short and medium term.